2015
DOI: 10.1186/s12963-015-0040-6
|View full text |Cite
|
Sign up to set email alerts
|

Erosion of the healthy soldier effect in veterans of US military service in Iraq and Afghanistan

Abstract: BackgroundThis research explores the healthy soldier effect (HSE) – a lower mortality risk among veterans relative to the general population—in United States (US) veterans deployed in support of operations in Iraq and Afghanistan (OEF/OIF/OND). While a HSE has been affirmed in other OEF/OIF/OND populations, US veterans of OEF/OIF/OND have not been systematically studied.MethodsUsing US Department of Veterans Affairs (VA) administrative data, we identified veterans who (1) had been deployed in support of OEF/OI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…These findings support an emerging literature that questions whether the HSE is as relevant for the newest generation of veterans as it once was. 2,32,33 Researchers from the VA note that "the healthy solider/worker effect gradually subdued over time." 33 VA data estimate that male and female veterans have fewer expected life years (0.8 and 1.2 years, respectively) than nonveterans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings support an emerging literature that questions whether the HSE is as relevant for the newest generation of veterans as it once was. 2,32,33 Researchers from the VA note that "the healthy solider/worker effect gradually subdued over time." 33 VA data estimate that male and female veterans have fewer expected life years (0.8 and 1.2 years, respectively) than nonveterans.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to a lack of clearly designated front lines and clear demarcation between enemy combatants and the civilians populations in which the enemy tended to embed; the higher number of war-zone tours; and longer deployments than earlier wars. 39 In addition, the wars in Iraq and Afghanistan relied more heavily on service members from National Guard and Reserve units that, in general, have a lower state of military preparedness 32 and less access to military institutional support mechanisms such as Family Readiness Groups that provide crucial social, economic, and emotional support before, during, and after deployment. 40 Emerging evidence suggests increased risks to health for Iraq and Afghanistan veterans who seem to have higher rates of tobacco and alcohol use, 32,41,42 known risk factors for CVD, and to early onset mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 On average, Veterans have had a lower mortality rate than the general public (referred to as the ''healthy soldier effect''), although this effect has, unfortunately, reversed for Veterans from recent conflicts. 26 Nearly half of Veterans are over age 65. Among Veterans in the labor force, unemployment rates are lower than for non-Veteran civilians, although Veterans covered by VA health care are unemployed at rates 50% higher than the general Veteran population and 20% higher than the civilian population.…”
Section: Tip 5: the Experience Of Each Veteran Is Uniquementioning
confidence: 99%
“…4 By comparison, active duty servicewomen may be healthier than the general population as a result of physical and educational requirements to enter military service. 26,27 What Is Known About Pregnant Veterans Using VA Maternity Care Benefits Veterans using VA coverage for their prenatal and delivery care have repeatedly been demonstrated to be a high-risk group (►Table 3). One of the earliest works looking at pregnancy and mental health among women Veterans returning from Iraq and Afghanistan compared 2,966 Veterans with any evidence of pregnancy-related diagnoses or care (e.g., positive pregnancy tests) in the VA to their nonpregnant peers, and found that Veterans with a pregnancy were twice as likely to have mental health diagnoses, including depression, anxiety, PTSD, or other serious mental illness.…”
Section: Who Takes Care Of Pregnant Veteransmentioning
confidence: 99%